CCAFS Household Baseline Survey 2010-2012 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
This dataset contains files produced for and generated from the CCAFS Household Baseline Survey which was run in 15 core sites across East & West Africa and South Asia. The survey was also carried out in several other sites in South Asia, Mozambique and Central America. Before downloading any of the files, particularly the data files, please download and read the CCAFS ReadMe file and the Data Quality summary which are both tagged as "CCAFS ReadMe".